Results of numerical modelling of the problem of video pulse ground penetrating radar research in freshwater bodies - Gulevich Oxana; Volkomirskaya Liudmila; Mingalev Igor; Varenkov Vladimir; Suvorova Zoya; Akhmetov Oleg; Mingalev Oleg; Gulevich Oxana (Russian Journal of Earth Sciences)
Ground-penetrating radar profiling on the surface of water bodies is applied in various geological and engineering studies. Here, we present the results of numerical simulation of the propagation of a video pulse electromagnetic signal in a freshwater body with gradients of the permittivity and electrical conductivity in the near-bottom layer. The method of numerical solutions of Maxwell's equations in the time domain is applied, in the general setting for rapidly changing processes, without restrictions on the magnitude of the change in the parameters of the medium. The results make it possible to explain the apparent decrease in water depth according to GPR data in comparison with the true depth and the appearance of additional reflecting boundaries on radargrams in the bottom layer.